Coverage of Mexico in United States media: Phases of academic scholarship. (December 2015) - Rendon, Hector; Johnson, Melissa A
This study summarizes the research produced from 1984 to 2014 about coverage of Mexico in the United States media. The most important findings are: in the last three decades there has been an exponential growth in academic production related to this topic; researchers working for public universities in border states (geographic proximity) or with high rates of Hispanics in the population (cultural proximity) are producing most of these studies; and there is a lack of studies related to the coverage of Mexico in United States digital media. Topics of academic interest clustered in four phases: Cultural Understanding Phase (1984–1993), NAFTA Phase (1995–1996), International and Cultural Integration Phase (1997–2010), and Threat Phase (2010–2014). The goal of the analysis was to discern trends, demonstrate research gaps, and facilitate academic collaboration. The article also notes the parallel between trends in academic work and patterns in journalism.